(untitled) (The Journal of Psychology and Sociology, 2022)
The article describes the difficulties in the psychological adaptation of mothers after childbirth, as well as the results of the study based on the use of the author’s questionnaire of subjective states and the Spielberger-Hanin anxiety scale. The aim of the study is to describe the characteristics of subjective experiences and psycho-emotional state, as well as the anxiety of mothers in the postpartum period. The article considers the main factors influencing the course of psychological adaptation in women, such as changes in hormonal levels, lack of support and help from relatives, the level of readiness for mother- hood, etc. In addition, possible changes in the psycho-emotional state of mothers and their manifesta- tions are described. The study involved 30 mothers of the city of Nur-Sultan aged 18 to 40 years. Ac- cording to the results of the study, it was revealed that the psycho-emotional state of mothers undergoes changes after childbirth, which directly complicates their psychological adaptation. Women become more irritable, nervous, vulnerable and aggressive. In addition, the study showed that more than half of the participants in the study experience high levels of anxiety. Early planning of motherhood and sup- port from relatives makes it easier to overcome difficulties in the psychological adaptation of mothers. Key words: perinatal psychology, postpartum period, psychological adaptation, psycho-emotional state, anxiety.